2014
DOI: 10.1371/journal.pone.0089672
|View full text |Cite
|
Sign up to set email alerts
|

3D Visualization of the Initial Yersinia ruckeri Infection Route in Rainbow Trout (Oncorhynchus mykiss) by Optical Projection Tomography

Abstract: Despite the fact that enteric redmouth disease (ERM) in farmed rainbow trout is one of the most devastating disease problems, little is known about the initial route of infection and pathogenicity of the aetiological agent, Yersinia ruckeri. In order to determine the initially infected organs, optical projection tomography (OPT), a novel three-dimensional (3D) bio-imaging technique, was applied. OPT not only enables the visualization of Y. ruckeri on mucosal surfaces but also the 3D spatial distribution in who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 49 publications
(65 reference statements)
3
47
0
1
Order By: Relevance
“…Its preferential mode of entry is through the gills, but it has also been described to infect the intestine through the mucosal tissue (Ohtani et al, 2014; Tobback et al, 2009, 2010). Despite these findings, few studies have described the immune response against ERM in fish GALT.…”
Section: Mucosal B Cell Responses In Gutmentioning
confidence: 99%
“…Its preferential mode of entry is through the gills, but it has also been described to infect the intestine through the mucosal tissue (Ohtani et al, 2014; Tobback et al, 2009, 2010). Despite these findings, few studies have described the immune response against ERM in fish GALT.…”
Section: Mucosal B Cell Responses In Gutmentioning
confidence: 99%
“…cytokines, transcription factors, acute-phase proteins, Toll-like receptors. Additionally, we have visualized the presence of serotonin in intestinal cells in zebrafish using optical projection tomography, a bioimaging method based on the use of specific antibodies that only recently have been implemented in fish immunology studies [14] [15]. Serotonin (5-HT) is a ubiquitous and highly conserved neurotransmitter that plays a pivotal role in a variety of behaviors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Up until now, literature describing Y. ruckeri infection in the CNS in rainbow trout has followed infection with virulent serotype O1 biotype 1 (Ferguson, ; Ohtani et al., ; Roberts, ). It has been demonstrated that Y. ruckeri serotype O1 biotype 1 strain 293/2003 appeared in the CNS at 7 dpi in rainbow trout fry following waterborne challenge, when fish suffered from systemic infection (Ohtani et al., ).…”
Section: Discussionmentioning
confidence: 99%